Threshold Techniques to Improve Sensing Under Noise Uncertainty in Cognitive Radio Networks - garg, Sakshi; Sharma, Muskan; Thagjam, Sharmelee (International Journal of Computer Sciences and Engineering, 2025)
Cognitive radio network is a network which overcomes the deficiency of spectrum in this fast-growing radio network. In this network, secondary users sense the spectrum that is used by primary users and if spectrum is vacant or not utilized then utilize the spectrum with proper management and sharing. For the foremost step sensing, different techniques are proposed but energy detector (ED) is most widely used due to its least sensing time requirement and low complexity. But there are limitations also; its performance degrades due to unknown variations in noise and this uncertainty cause problem of SNR wall and problem in achievement of exact energy threshold. Till now, various approaches have been proposed to accomplish better performance of system under low SNR environment. So, to increase the throughput and efficiency of system double threshold, dynamic threshold, two stage spectrum sensing etc. techniques have been proposed to alleviate above mentioned problems and also mathematical relation between energy threshold, probability of detection and false alarm is considered.